Moral Disengagement in Middle School Students: Survey in Religious Education - ., Yufiarti; Nuraini, Sri; Solihin, Muhammad; Rachmadtullah, Reza (International Journal of Engineering and Technology, 2018)
Indonesian culture has many schools which based on religion. The main objective of the Islamic school is to make their students have moral or wonderful behavior. The purpose of this study was to investigate moral disengagement of students at religious education. This survey on 171 students included female and male. Data analysis used descriptive as graph and percentage. Children can enroll to the religious schools. Profile shows that many children varieties such as gender, age. Student’s at moral disengagement was multiple diverse.